Expediting COD removal in microbial electrolysis cells by increasing biomass concentration - Aboutalebi, Hanieh; Sathasivan, Arumugam; Bal Krishna, K.C.; Jabari Kohpaei, Ahmad (Elsevier BV, 2011)
Microorganisms catalyse the reaction and in this study, mainly the effect of different concentration of biomass on COD removal was investigated. Three sets of two-compartment reactors were established. The cation exchange membrane (CEM) was employed in each reactor and 0.5. V of electricity was supplied. Graphite rod employed in cathodic part and a combination of graphite rod and graphite granules were used in anodic chamber. The highest rate of COD removal (40. 2.0. ppm/h) was achieved in the reactor which had initial VSS at 6130. mg/l, whereas the slowest rate of 23. 1.2. ppm/h in the reactor started with 3365. mgVSS/l. Some ammonia removal was also noticed during the operation. Further understanding and improvement is needed to be competitive against traditional wastewater treatment processes.